Penurunan Keluhan Dribbling Pasien Pasca Transurethral Resection Of The Prostate Melalui Kegel’s Excercise - Abdul Madjid; Dewi Irawaty; Tuti Nuraini (Jurnal Keperawatan Indonesia, 2011)
AbstrakPenelitian ini bertujuan untuk mendapatkan gambaran pengaruh Kegel’s exercise terhadap keluhan dribbling pasien pascatransurethral resection of the prostate (TURP). Sampel penelitian adalah responden yang dirawat di RS X dan RS Y yangmemenuhi kriteria inklusi. Jumlah sampel pada kelompok intervensi sejumlah 10 responden, sedangkan kelompok kontrol 10responden. Hasil penelitian menunjukan keluhan dribbling pada kelompok intervensi berhenti mulai hari ke-13, sedangkanpada kelompok kontrol berhenti mulai hari ke-24, sehingga membuktikan ada perbedaan yang signifikan rata-rata lama keluhandribbling antara kelompok intervensi dan kelompok kontrol (p= 0,007; α= 0,05). Penurunan lama keluhan dribbling padaresponden yang patuh melakukan Kegel’s exercise berhenti mulai hari ke-13, sedangkan pada responden yang tidak patuhberhenti mulai hari ke-20, sehingga membuktikan ada perbedaan yang bermakna rerata lama keluhan dribbling responden yangpatuh melakukan Kegel’s exercise dengan responden yang tidak patuh (p= 0,004; α= 0,05). Simpulan dari penelitian ini adalahKegel’s exercise terbukti dapat menurunkan keluhan dribbling pasien pasca TURP. Disarankan agar tiap rumah sakit dapatmenerapkan Kegel’s excercise terhadap pasien dengan keluhan dribbling pasca-TURP.Kata Kunci: Kegel’s exercise, keluhan dribbling, pasca transuretral resection of the prostate (TURP), patuh Kegel’s exerciseAbstractThis study aims to see the effect of Kegel’s exercise on Dribbling Complaint of Post Transurethral Resection of the Prostate(TURP) patient. The sample was the patients who are hospitalized in X hospital and Y hospital fulfill the inclusion criteria.There were 10 responden each for intervention and control groups. The study results show that dribbling complaint of patientin intervention group stop at day 13, while in control group stop at day 24. Thus, there is a significant difference of the averageof dribbling complaint duration between intervention and control groups (p= 0.007; α= 0.05). In addition, for the respondentsin intervention group who did the exercise regularly, the dribbling complaint stop at day 13 and those who did not do exerciseregularly the complaint stop at day 20. This is shown again that there is a significant difference of the average of dribblingcomplaint duration between those who do the exercise regularly and who do not do it regularly (p= 0.004; α= 0.05). Inconclusion, the Kegel’s’s exercise is proven can reduce the dribbling complaint of post TURP patient. It is recommended thateach hospital can apply Kegel’s excercise for patients with symptoms of post-TURP dribbling.Key words: Kegel’s’s exercise,